DISCRIMINANT ANALYSIS AND MAHALANOBIS DISTANCE (NIR DIFFUSE REFLECTANCE SPECTRA) IN THE ASSESSMENT OF DRUG’S BATCH-TO-BATCH DISPERSION AND QUALITY THRESHOLD ESTABLISHMENT - Morozova, Maria; Elizarova, Tatyana; Pleteneva, Tatyana (European Scientific Journal, ESJ, 2013)
Distance-based supervised pattern recognition method (PRM) – discriminant analysis (DA) in principal component (PC) space described by Mahalanobis distance (MD) - was suggested for definition of batch-to-batch dispersion of 22 drugs, produced by 14 manufacturers. The range of under test medicines numbered 18 pharmacological classes, including biologics, microbiological drugs and combined drugs, containing several active ingredients. Thermo Scientific ANTARIS II FT-NIR Analyzer collected spectra in diffuse reflectance mode, data pre-processing and analysis were performed using the TQ Analyst software. The value of spectral dispersion for the most samples in the research except capsules did not exceed 10 MD, what correlated with the values met in literature (Mark & Tunnell, 1985). Mahalanobis distance threshold, which was calculated in leave-one-out-cross validation (LOOCV), proved equal 3 for the majority of drugs, what was in a good agreement with the theoretically determined limit (Mark, 2001, p. 321).